Phototherapy of Brain Tumours Using a Fibre Optic Neurosystem - Yuliya Maklygina (MDPI AG, 2021)
In this work, a new approach was tested to assess the cellular composition of tissues by time-resolved methods of fluorescence analysis of exogenous and endogenous fluorophores. First of all, the differences in fluorescence kinetics of endogenous fluorophores (coenzymes NADH and FAD) in tumour and immunocompetent cells were determined. After that, differences in fluorescence kinetics of photosensitizer 5 ALA-induced protoporphyrin IX were established due to its different metabolism in cells of different phenotypes. Kinetics of photoluminescence of NADH and FAD coenzymes as well as photosensitizer were studied by means of two different methods: time-resolved spectroscopy based on a streak-camera and fibre optic neuroscopy, which served to perform process monitoring and regular fluorescence diagnosis of the probed region. Time-resolved fluorescence microscopy (FLIM) was used as a control technique. Time-resolved spectroscopic fluorescence lifetime analysis was performed on sexually mature female rats induced with glioma C6 brain tumour under in vivo conditions; thus, under conditions where the immune system actively intervenes in the process of oncogenesis. In this regard, the aim of the study was to recognize the cellular composition of the brain tumour tissue, namely the ratio of cancer and immunocompetent cells and their mutual localization. Understanding the role of the immune system thus provides new ways and approaches for further diagnosis and therapy, making tumour-associated immune cells a prime target for modern therapies.